2018
DOI: 10.1101/467027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple Duration Priors Within and Across the Senses

Abstract: Perception can be understood as an active process in which sensory samples are combined with prior expectations to shape perceptual content. A prominent example of the influence of priors on perception is that manually reproduced temporal durations are biased towards the mean of previously experienced durations. However, little is known about how prior expectations are acquired and maintained in environments in which multiple competing cues may indicate whether a given prior should be applied in that specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 93 publications
2
21
2
Order By: Relevance
“…The general overestimation we found in the behavioral results might potentially be explained by the integration of these visual stimuli in temporal estimation (Shi & Burr, 2016). Future studies might look further into potential modality differences in contextual calibration and their neural underpinnings (Rhodes, Seth, & Roseboom, 2018;Roach et al, 2017). Furthermore, we found no significant decoding corresponding to the windows of CNV differences.…”
Section: Discussioncontrasting
confidence: 54%
“…The general overestimation we found in the behavioral results might potentially be explained by the integration of these visual stimuli in temporal estimation (Shi & Burr, 2016). Future studies might look further into potential modality differences in contextual calibration and their neural underpinnings (Rhodes, Seth, & Roseboom, 2018;Roach et al, 2017). Furthermore, we found no significant decoding corresponding to the windows of CNV differences.…”
Section: Discussioncontrasting
confidence: 54%
“…Adding additional cues that potentially help participants to distinguish between temporal contexts did not improve the separation of both sets of intervals. These results are interesting as earlier work (e.g., Rhodes et al, 2018) has shown that unique prior distributions can be formed when intervals are defined by physical properties of the signal. This work indicates that presenting "blocks-of-trials" is sufficient to generate unique prior distributions, and adding additional cues to aid categorization did not affect the prior distributions sufficiently to be reflected in central tendency related statistics in this study.…”
Section: Discussionmentioning
confidence: 53%
“…When physical properties of the stimuli are not indicative of the context, other aspects need to be sufficiently distinct between contexts to obtain a temporal context effect. In how far statistical properties of the stimulus material (i.e., the distributions of durations) have to differ between contexts has recently received some attention in literature (e.g., Acerbi et al, 2012;Rhodes, Seth, & Roseboom, 2018;Roach et al, 2017). For example, Rhodes et al (2018) demonstrated that the behavior of human participants was best described by a Bayesian Observer Model that assumed a different prior based on the specific parameters of the presented signal (i.e., visual flashes or auditory tones, high or low pitch tones, or white noise versus pure tone audio).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations